LABEL DESIGNING FOR MINIMALLY PROCESSED TILAPIA AIMING THE TRACEABILITY OF THE PRODUCTIVE CHAIN - MACIEL, ERIKA DA SILVA; VASCONCELOS, JÚLIA SANTOS; SAVAY-DA-SILVA, LUCIANA KIMIE; GALVÃO, JULIANA ANTUNES; SONATI, JAQUELINE GIRNOS; CHRISTOFOLETTI, JEFFERSON CRISTIANO; OETTERER, MARÍLIA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2012)
The aim of this study was to develop label for Nile tilapia minimally processed. Analyses were performed to quantify the nutritional components of the fillets; and information about freshness, date of processing and batch specification was collected. Such data were essential for designing labels providing information about the traceability system and presenting codes for quality identification such as the Quick Response Code (QR Code), which allows the electronic encoding of the product on a database. Mandatory food labeling associated with the use of QR Code are tools that convey information to consumers about food quality and the entire production chain. One hundred sixty-two potential consumers were surveyed about the general characteristics of the product packaged in poly nylon film type, vacuum-packed, used for the packaging of traced fresh-cut fillets of tilapia minimally processed and kept under refrigeration (0±1oC). According to the Spearman correlation the variables packaging, general appearance and willingness to purchase the product presented a correlation, with coefficients estimated at 0.437, 0.466 and 0.497 respectively.